Islamic civilization and globalization in the modern era - Pulungan, Muhammad Syukri (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: The issue of globalization is a concern in various aspects ranging from economics, politics and culture. Recognizing the fact that globalization comes from rich and powerful countries in the West that indirectly replace traditional values in the East with foreign values by marginalizing local culture. Meanwhile, the values transferred through globalization tend to be value-free and not in accordance with religious values, morals and local wisdom. Methods: To counter the world's injustices, especially in the economic and political fields, it is necessary to develop global ethics from existing cultures and civilizations in the world. This involves formulating a vision of global transformation based on ethical awareness, applicable at the world, national, or local levels, encompassing both men and women. Results: This research underscores the importance of establishing basic ethical values, criteria, and common attitudes for peaceful coexistence in response to the challenges posed by globalization. Conclusion: The development of global ethics is crucial for addressing the disparities and injustices brought about by globalization, ensuring that ethical awareness and local wisdom are incorporated into global interactions.